(3JeQjf GdWdGH aj UfGYI GdEYQGHs - (3GdLQLGhj GdCRgQj GdeUQj, Rjf GdOjf, GdhbGO, NGdO Hf YHO Gddg Hf CHj HcQ, J (B905 (3g`s ((3GHf YHO Gddg (B((3GdcQOj(B)s)
(3ChdgG (B:s
(3GdMeO ddg GdPj QaY bOQ ef CYQH HGdTgGOJjf(B...(3CeG HYO aEf eYQaI GdEYQGH ef GdhGLHGJ GdJj dG HO dcd WGdH Yde efgG(B...s
(3BNQgG (B:s
(3hbGd GdTGWHj(B: (3HYO Cf fbd Cfg GSe eUOQ hjMJed Cf jVHW gfG HaJM GdNGA(B...(3hgPG BNQ eG CQOfG LeYg aj gPG GdeNJUQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B297s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B668s
(3cTa GdXfhf(B:(3L(B1(3,U(B483s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdfMhs